Inhibitors of tumor necrosis factor-α and mechanisms of their action - Bufan, Biljana; Jančić, Ivan; Stojić-Vukanić, Zorica (Archives of Pharmacy, 2020)
Tumor necrosis factor (TNF)-α is a proinflammatory cytokine with a role in immunity to pathogens, as well as in the pathogenesis of several autoimmune/inflammatory diseases. Biological drugs targeting this cytokine and inhibiting its effects are designed. Until today, five TNF-α inhibitors are approved: infliximab, adalimumab, golimumab (monoclonal antibodies), certolizumab pegol (pegylated antigen-binding fragment of immunoglobulin), and etanercept [TNF receptor type 2-fragment crystallizable (Fc) of immunoglobulin fusion protein]. Their approved biosimilars are on the market, too. They are mainly used for the treatment of rheumatoid arthritis, inflammatory bowel disease, and psoriasis. Although TNF-α inhibitors are present in clinical practice for more than two decades and are established as an efficacious therapeutics, researchers are still occupied by revealing the complex mechanisms of their action. Namely, in addition to binding and neutralisation of soluble TNF-α, these drugs also bind/block transmembrane form of TNF-α (tmTNF-α), trigger diverse intracellular signals in tmTNF-α positive cells (a process named “reverse signalling”) or, if they have an Fc fragment, mediate killing of tmTNF-α-expressing cells by other immune cells or the complement system. Also, TNF-α inhibitors that contain Fc portion of the IgG antibody may affect Fc receptor-expressing cells and have an effector function quite independent of their TNF-α neutralisation capacity.
Keywords: TNF-α inhibitors; TNF-α neutralization; TNF receptors; transmembrane TNF-α